THE ROLE OF CAREGIVER COMMUNICATION IN SHAPING INDEPENDENT ATTITUDES IN FOSTERED CHILDREN (CASE STUDY AT THE PUTRI SITI AISYAH AEK KANOPAN ORPHANAGE) - Zulia Fitri Ritonga; Zuhriah Zuhriah (Program Pascasarjana UIN Sumatera Utara, 2025)
Children living in orphanages generally come from underprivileged family backgrounds and therefore require special attention and guidance. This study aims to analyze the role of caregiver communication in shaping the independence of foster children at Putri Siti Aisyah Orphanage in Aek Kanopan. This research uses a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation. The findings show that caregivers train the children to become independent by instilling discipline in daily activities. The communication established between caregivers and foster children plays a crucial role in fostering the children's independence. The communication approach adopted by caregivers combines both humanistic and authoritative methods, emphasizing empathy as well as firmness in nurturing. The foster children exhibit positive development in terms of behavior, responsibility, and social skills. Communication challenges such as the children's reserved attitudes, diverse backgrounds, and environmental influences can be overcome through patient and consistent communication. This study affirms that caregivers function not only as guides but also as companions who support the process of developing children's independence. The findings highlight the importance of continuous and effective communication in supporting the growth of foster children into self-reliant individuals.